Oxidative and nitrosative signaling in plants: Two branches in the same tree? - Fotopoulos, Vasileios; Molassiotis, Athanassios (My University, 2011)
Reactive oxygen species (rOS) and reactive nitrogen species (rNS) constitute key features underpinning the dynamic nature of cell signaling systems in plants. Despite their importance in many aspects of cell biology, our understanding of oxidative and especially of nitrosative signaling and their regulation remains poorly understood. Early reports have established that rOS and rNS coordinately regulate plant defense responses to biotic stress. in addition, evidence has accumulated demonstrating that there is a strong cross-talk between oxidative and nitrosative signaling upon abiotic stress conditions. The goal of this mini-review is to provide latest findings showing how both rOS and rNS comprise a coordinated oxidative and nitrosative signaling network that modulates cellular responses in response to environmental stimuli
Keywords: Abiotic stress; Nitrosative stress; Oxidative stress; Reactive nitrogen species; Reactive oxygen species; Signaling